2019
DOI: 10.1002/ase.1920
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Ceremony in Honor of the Body Donors in the Development of Ethical and Humanistic Attitudes among Medical Students

Abstract: Activities related to body donation programs, such as donor memorial ceremonies, provide the opportunity to complement student training, especially with regard to the ethical and humanistic elements involved in medical training. This study sought to assess the impact of a ceremony in honor of the body donors has on ethical and humanistic attitudes in medical students. Medical students were surveyed about their perceptions of changes in themselves, respect for donors and donor families, and their relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
16
0
2
Order By: Relevance
“…The existing body of literature as well as this study, highlight that students perceive having personal information, that is, name, motivation to donate, and donor's biography as important to fulfill the humanizing goals of modern anatomy (Jones and King, 2017; da Rocha et al, 2020). The theme of heightened responsibility and reflection is also highlighted in other studies in anatomy education all of which emphasize the importance of the humanistic approach (Winkelmann and Güldner, 2004; Lin et al, 2009; Chiou et al, 2017; Štrkalj and Pather, 2017).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The existing body of literature as well as this study, highlight that students perceive having personal information, that is, name, motivation to donate, and donor's biography as important to fulfill the humanizing goals of modern anatomy (Jones and King, 2017; da Rocha et al, 2020). The theme of heightened responsibility and reflection is also highlighted in other studies in anatomy education all of which emphasize the importance of the humanistic approach (Winkelmann and Güldner, 2004; Lin et al, 2009; Chiou et al, 2017; Štrkalj and Pather, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…The study also reported that the commemoration encouraged students to reflect on ethical issues as well as a heightened sense of commitment and responsibility regarding their own learning (da Rocha et al, 2018). In another study by da Rocha and colleagues, it was suggested that a commemoration would promote greater personification of the donor as a consequence of being surrounded by donors' families thus reinforcing the long‐term bond and ethical attitude (da Rocha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy laboratory‐based outreach programs' goals are to expose high school and undergraduate university students to health professions and health professional education (Healy, 2011; Zhang et al, 2016; Meyer et al, 2018; Wines, 2019), provide educational opportunities for underserved students (Meyer et al, 2018; Wines, 2019), foster curiosity about human anatomy and pathology through active learning and hands‐on experience (Zhang et al, 2016; Wines, 2019; Reed, 2020), increase health literacy (Meyer et al, 2018), and inform the public about whole body donation programs for education and research (Healy, 2011). At the Federal University of Health Sciences of Porto Alegre in Brazil, exemplary dissections completed by undergraduate students are temporarily displayed each year in the “Museum of Anatomy,” which members of the general public may visit, with the intended purpose being to inform them about the university's body donation program (da Rocha et al, 2020). While the goals of anatomy laboratory‐based outreach programs are well publicized, the effectiveness of these programs in achieving these goals is minimally documented.…”
Section: Introductionmentioning
confidence: 99%
“…Students have often felt inspired to honour the cadaver who was their first teacher during the medical schooling years. Respecting the cadavers, the knowledge they bring in the subject of anatomy is a must and will promote further body donations by the general public [22][23][24][25]. Ceremonies to celebrate the donated cadavers have an inspirational effect on the medical students and could promote ethical and humanistic attitude among the medical students [26][27][28][29][30][31].…”
Section: Several Countries Have No Body Donation Program In Placementioning
confidence: 99%